Implementation processes of site-based management at schools in challenging circumstances in Germany: Principals' and teachers' perceptions of openness and consensus in target setting processes. (September 2021) - Lee, Eunji; Neumann, Marko; Boese, Susanne; Maaz, Kai
Highlights: Measures of site-based management for advancing school development. Collaboration and cooperation within faculty important for implementation processes. Importance of faculty characteristics for implementation processes. Limited correspondence of principals' and teachers' perceptions. Abstract: The present study aimed at investigating implementation processes of a program of site-based management. In the context of the German Bonus Program – a measure of site-based management in Berlin – data from N = 52 principals and N = 487 teachers were used. Focusing on the degree of cooperation and collaboration exercised in these processes, both openness and consensus within the program's target setting process were examined. The analyses included descriptive, correlation, and regression analyses in order to determine the degree of openness and consensus, as well as relating factors of the faculty to these variables. Additionally, principals' and teachers' perspectives were compared. The results show a high degree of openness and consensus in the target setting process. We further found moderate associations between principals' and teachers' ratings and differing relational patterns for principals and teachers, indicating limited correspondence of principals' and teachers' perceptions on the school level.